Accounting for Ecosystem Restoration: Assessing the Financial and Social Impacts of the Program at Rimbo Panjang Village - Fifitri Ali (Politeknik Caltex Riau, 2025)
Method - Utilizes a qualitative approach with secondary data analysis from financial records, NGO reports, and regional socio-economic indicators. Key Findings - The project exhibited financial transparency, but gaps in report consolidation, income tracking, and variance analysis were identified. Social benefits, such as improved income and community resilience, were observed, though not monetarily quantified. Environmental metrics, including ecosystem service valuation and sustainability indicators, were absent. Theoretical and Policy Implications - Highlights the need for structured accounting practices, including SROI and cost-benefit analysis, to enhance sustainability, transparency, and stakeholder engagement in local environmental projects. Research Novelty – This study provides a new perspective on how environmental accounting can integrate financial, social, and ecological evaluations in peatland restoration projects at the village level, while emphasizing its crucial role in supporting sustainable ecosystem management.